Representations of the Philippine Stock Market and Securities Research, and Global Financial Regularization - Tolosa, Benjamin T, Jr (Archīum Ateneo, 2004)
While the current turmoil in global finance seems to support calls for “transparency,” “accountability,” and “professionalization,” closer analysis reveals disjunctures in the dominant discourse on corporate governance, whose central element is the promotion of “investor confidence” and “shareholder value.” This essay draws on the theoretical work of Pierre Bourdieu and Stuart Hall to examine how representations of the stock market and securities research in the Philippines regularize particular interests, identities, relations, and hierarchies in the global political economy. But it also shows how these representations reveal underlying tensions in the discourse that open up spaces for rearticulating and reordering financial governance.